2020
DOI: 10.3390/antibiotics9090610
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care C-Reactive Protein Testing to Reduce Antibiotic Prescribing for Respiratory Tract Infections in Primary Care: Systematic Review and Meta-Analysis of Randomised Controlled Trials

Abstract: C-reactive protein (CRP) point-of-care testing (POCT) is increasingly being promoted to reduce diagnostic uncertainty and enhance antibiotic stewardship. In primary care, respiratory tract infections (RTIs) are the most common reason for inappropriate antibiotic prescribing, which is a major driver for antibiotic resistance. We systematically reviewed the available evidence on the impact of CRP-POCT on antibiotic prescribing for RTIs in primary care. Thirteen moderate to high-quality studies comprising 9844 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 86 publications
2
62
0
1
Order By: Relevance
“…В снижение частоты необоснованной антибактериальной терапии при инфекциях дыхательных путей существенный вклад вносит возможность лабораторной экспресс-диагностики. Исследование уровня лейкоцитов у детей с лихорадкой и симптомами респираторной инфекции длительностью не менее 48 ч и исследование С-реактивного белка в сыворотке крови значительно снижают риск назначения АБП при первичной консультации [21,22]. Стоит отметить, что для достижения положительного влияния лабораторных исследований на амбулаторное лечение респираторных инфекций необходимо проведение обучения врачей интерпретации результатов исследования, так как часто cut-off-уровень (пороговое значение) для исключения возможного бактериального воспаления не совпадает с референсными значениями анализов.…”
Section: ограничения исследованияunclassified
“…В снижение частоты необоснованной антибактериальной терапии при инфекциях дыхательных путей существенный вклад вносит возможность лабораторной экспресс-диагностики. Исследование уровня лейкоцитов у детей с лихорадкой и симптомами респираторной инфекции длительностью не менее 48 ч и исследование С-реактивного белка в сыворотке крови значительно снижают риск назначения АБП при первичной консультации [21,22]. Стоит отметить, что для достижения положительного влияния лабораторных исследований на амбулаторное лечение респираторных инфекций необходимо проведение обучения врачей интерпретации результатов исследования, так как часто cut-off-уровень (пороговое значение) для исключения возможного бактериального воспаления не совпадает с референсными значениями анализов.…”
Section: ограничения исследованияunclassified
“…Evidence from these systematic reviews on immediate antibiotic prescribing showed that POC tests for CRP were associated with a risk ratio of 0.81 (95% CI, 0.71 to 0.92) 27 in ambulatory care settings (i.e., outpatient settings, walk-in clinics, or emergency departments) and a risk ratio of 0.79 (95% CI, 0.70 to 0.90) 54 in primary care settings more generally. Therefore, POC tests for CRP likely reduce antibiotic prescribing at the point where people seek care compared with usual care without a POC test.…”
Section: Immunoassay-based Poc Testsmentioning
confidence: 99%
“…Inappropriate rates of antibiotic prescription have been observed across several healthcare settings, from primary to secondary care, with a particular focus being placed on primary care [ 8 ]. Several studies have shown promise with regards to the use of ASP interventions in the primary care setting [ 9 , 10 , 11 ]. Further, recent reviews exploring paediatric ASPs in both inpatient and outpatient settings have observed the potential of these interventions in reducing antimicrobial use, healthcare costs and AMR [ 12 ].…”
Section: Introductionmentioning
confidence: 99%